A mixed-methods evaluation of the ¡Vamos por Más! parenting program implementation in Chile. Issue 1 (14th March 2023) - Meyer, Jessica K.V.; Diaspro, Gabriela; Muñoz, Iván; Burmeister, Catalina; García-Huidobro, Diego
ABSTRACT: Introduction and aims: Substance use is a significant global concern. Strengthening parenting in families with adolescents has been shown to reduce substance use initiation. The ¡Vamos por Más! (¡VxM!) program is a positive-parenting program developed in Chile to improve family relations and reduce adolescent substance use that combines in-person school workshops, multimedia messaging and personalized support. This manuscript reports a mixed-methods evaluation of the pilot implementation of the ¡VxM! program utilizing the Consolidated Framework for Implementation Research and Proctor's taxonomy for process outcomes. Methods: An explanatory sequential design was used. Quantitative methods evaluated program use, acceptability, appropriateness, and fidelity, and were followed by qualitative focus groups (FGs) to assess the implementation process and understand these outcomes. Thirteen FGs stratified by school and role, including school leaders, program facilitators, participants, and researchers, were conducted. Results: The program was implemented in three schools, reaching 253 families with in-person workshops (40.5% of potential participants), 257 parents who viewed on average 72.1% of sent multimedia messages, and 2 families who used the personalized support (0.3%). Overall, the program was viewed as acceptable and appropriate by participants and implementers due to the high quality of program materials, targeted content, and activities. Implementation differed by schools. Key implementation factors were the outer context, inner school setting, and implementation processes. Conclusions: This comprehensive evaluation, including both intervention implementers and participants, identified implementation facilitators, barriers, and outcomes. Future ¡VxM! implementations should alter program components of schools with lower engagement to improve program implementation and outcomes.